Ambient air pollution undermines chemosensory sensitivity – a global perspective - Anna Oleszkiewicz; Andrea Pozzer; Jonathan Williams; Thomas Hummel (Scientific Reports)
Abstract This study offers insights into the complex relationship between chemical species constituting air pollution and chemosensory function. We examined the relationship between chemical species known to contribute to air pollution and assault human health and chemosensory sensitivity. Chemosensory sensitivity data was retrieved from a large-scale study involving 711 urban-dwelling participants inhabiting 10 different regions of the globe. Their olfactory threshold towards phenyl ethyl alcohol (PEA) and olfactory/trigeminal threshold towards Eucalyptol was measured in a multicentre study. We matched the individual chemosensory data with the levels of PM2.5, PM10, O3, NO2, SO2, CO at the location of testing sites, on the exact date of the test, using EMAC (ECHAM5/MESSy for Atmospheric Chemistry) model. Our findings indicate that air pollution negatively affects olfactory function and has cumulative negative effects with aging. The reported patterns are seasonal and increase during Autumn and Winter, and interact with medical conditions related to poorer olfactory function. We extend the current knowledge by demonstrating that olfactory/trigeminal perception is also disrupted by toxic air, albeit in a slightly different manner. The analyzed models promote a more complex perspective on the relationship between air composition and chemosensory sensitivity, but delineate problems related to the interdependence of the levels of chemical species constituting air pollution and using them together to predict chemosensory sensitivity. Conclusions point to the need to investigate the problem of air pollution and chemosensory health from a global perspective, as air quality partly accounts for the differences in chemosensory perception in different regions of the world.